The influence of social interaction, social influence and smartphone usage convenience towards smartphone dependency among Generation Y in Sungai Petani / Aini Najihah Ahamad and Nor Khanim Mohd Jafri - Ahamad, Aini Najihah; Mohd Jafri, Nor Khanim (2019)
This chapter provide an overview of the study which consists ten main sections this chapter identity the background of the study ascertain the research problem, research question and the research objective of the research endeavor. It also highlight the significant scope of the study provide definition of terms, and concept used in this study